Decídetexto México: Recruitment and baseline characteristics of Mexican individuals who smoke in a cessation study - Rosibel Rodríguez-Bolaños; Paula Ramírez-Palacios; Alejandra Bolaños; Daimarelys Lara; Gabriel Millan; Katia Gallegos-Carrillo; Yvonne N Flores; Raúl M Mejia; Ana Paula Cupertino; Francisco Cartujano-Barrera (SAGE Publishing, 2023)
The objective of this study was to evaluate the effectiveness of digital and traditional methods and strategies in the recruitment of Mexican individuals who smoke into a cessation study. Recruitment method refers in general to either digital or traditional recruitment. Recruitment strategies refer to the particular recruitment type utilized within each recruitment method. Traditional recruitment strategies included radio interviews, word of mouth, newspaper advertisement, posters/banners placed in primary healthcare clinics, and medical referrals. Digital recruitment strategies involved emails and study advertisements through social media (i.e., Facebook, Instagram and Twitter) and website. In a 4-month period, 100 Mexican individuals who smoke were successfully enrolled into a smoking cessation study. The majority of participants were enrolled via traditional recruitment strategies (86%) compared to the digital recruitment strategies (14%). Individuals screened in the digital method were more likely to be eligible to participate in the study, compared to the traditional method. Similarly, in comparison to the traditional method, individuals in the digital method were more likely to enroll in the study. However, these differences were not statistically significant. Both traditional and digital strategies made important contributions to the overall recruitment effort.